Review of public health and productivity benefits from different urban transport and related land use options in Australia - Matan, Annie; Trubka, Roman; Newman, Peter; Vardoulakis, S. (AST Management Pty Ltd, 2012)
The relationship between public health, urban forms and transportation options in Australia is examined through a review aimed at determining possible health indicators to be used in assessing future land use and transportation scenarios. The health benefits, and subsequent economic benefits of walkable, transit orientated urban forms are well established and are measurable. Important health indicators include vehicle miles travelled, access to public transport, access to green areas, transportation related air pollution levels, transportation related noise levels, density and mixed land use. A comparison between a high walkability urban environment and a low walkability urban environment identifies various infrastructure, transportation greenhouse gas emissions and health costs. From this it is determined that infrastructure and transport costs dominate, health costs are relatively small and that health-related productivity gains associated with highly walkable urban areas are substantial. This review provides heath and economic rationale for developing urban forms geared towards active travel.